AB0492 Long term safety of anti-TNF alfa in patients with inflammatory arthritis and hbv infection: Focus on hepatitis B surface antibody status. (23rd January 2014) - Tirri, R.; Stornaiuolo, G.; Sessa, P.; Puca, I.; Brancaccio, G.; Gaeta, G.B.; Valentini, G.
Abstract : Background: The rate of viral reactivation in occult HBV carriers (HBsAg-/HBcAb+) in the course of immunosuppressive therapy ranges from 5% to 10%.(1) Nevertheless, anti-TNFalpha therapy was reported to be quite a safe option in HBV occult carriers (i.e. HBsAg-; HBcAb+) patients in Italy(2). Recent data from Taiwan (Cina) pointed out the occurrence of viral reactivation in 1/12 HBV occult carriers patients with Rheumatoid Arthritis (RA) undergoing such treatment(3). Objectives: This abstract is devoted to furtherly address this topic. Methods: Three hundred and three patients(164F, aged 52, 4±12, 8) with RA or Spondylarthritis (SA) observed from May 2002 to July 2011, were administered anti-TNFalfa treatment for 42±30, 5 months. Serological screening for HBV infection with hepatitis B surface antigen (HBsAg), antibody against hepatitis B core antigen (anti-HBc) and hepatitis B surface antibody (anti-HBs) was performed in all patients. Moreover, Aminotransferases (ALT, AST) were evaluated at baseline and every 4 weeks. Finally, HBV-DNA evaluation was planned in HBcAb+ HBsAb+/- patients if transaminases would have increased >2 upper normal value in two consecutive determinations. Results: Fifty out of the 303 patients investigated, (25F, aged 58, 1±11, 2) (16, 5%) were HBsAg-/HBcAb +. Out of them 37 were HBsAb + (74%);10 HBsAb- (20%);in 3 patients HBsAb was not available. Ten patients were treated with IFX, 19 with ETA, 17 with ADA and 4 with GOL for 44, 5±28, 3 months. Twelve patients were also treated with Methotrexate (MTX), 4 with Leflunomide (LFN) and 11 with Prednisone (PDN) (<7.5mg/day). None of them underwent antiviral prophylaxis. Five patients developed an increase in ALTx 2 normal value in 2 consecutive determinations: 4 were HBsAb+ and 1 was HBsAb-.HBsAg positivity and HBV-DNA were not detected in any of them. ALT value reverted to normal in all patients by reducing or discontinuing MTX temporarily. Conclusions: Our results support the safety of long term anti-TNFalpha treatment in patients with inflammatory arthritis and HBV occult infection whichever is the HBsAb status. References: Charpin C. et al. Safety of TNF-blocking agents in rheumatic patients with serology suggesting past epatiti B state:results from a color of 21 patients. Arthritis Res Ther 2009, 11:R179. Caporali R et al. Safety of tumor necrosis factor α blockers in hepatitis B virus occult carriers (hepatitis B surface antigen negative/anti-hepatitis B core antigen positive) with rheumatic diseases. Arthritis Care Res. 2010, 749-754. Joung-Liang Lan et al. Kinetics of viral loads and risk of Hepatitis B virus reactivation in Hepatitis B core antibody-positive rheumatoid arthritis patients undergoing anti tumor necrosis factor alpha therapy.Ann Rheu Dims 2011;70:1719-1725. Disclosure of Interest: None Declared